Harga Saham Sektor Kesehatan: Faktor Rasio Keuangan - Abdul Latif; Iglesias Enmart Jeremia; Desma Natalia Hutauruk; Rina Azzahra Fili (Universitas 45 Surabaya, 2022)
At the beginning of the Covid-19 pandemic in 2020, all sectors of the national and global economy were wholly paralyzed, the impact of which was that the economy's pace was hampered due to the limited space for economic transactions. During the soaring cases of Covid-19, not all parties are harmed, one of which is the health sector, which has increased its operational rate amid the pandemic. Furthermore, the health sector in the capital market has become the target of local and foreign investors. From the description above, this study intends to analyze the variable debt-to-asset ratio, return on equity, and current ratio on the stock price of the health sector. The research method is associative quantitative with multiple linear regression models on the SPSS 25 statistical tool. The population and sample in this study are health sector companies listed on the Indonesian stock exchange. The results show that the return on equity variable does not affect the health sector stock price. In contrast, the debt-to-equity ratio and current ratio variables positively affect the health sector stock price.